Initial Volleyball Training And Its Essence - Turapova Shokhsanam Kholmurodovna (Periodica Journal, 2024)
This article deals with the development of technical preparation, organizing, their training, the aim and task of training, the aids of it
Keywords: Training; technical preparation; initial teaching